2018
DOI: 10.1155/2018/7295460
|View full text |Cite
|
Sign up to set email alerts
|

CT Myocardial Perfusion Imaging: A New Frontier in Cardiac Imaging

Abstract: The past two decades have witnessed rapid and remarkable technical improvement of multidetector computed tomography (CT) in both image quality and diagnostic accuracy. These improvements include higher temporal resolution, high-definition and wider detectors, the introduction of dual-source and dual-energy scanners, and advanced postprocessing. Current new generation multidetector row (≥64 slices) CT systems allow an accurate and reliable assessment of both coronary epicardial stenosis and myocardial CT perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 123 publications
(172 reference statements)
0
30
0
6
Order By: Relevance
“…It is important to note, however, that despite the growing evidence supporting the diagnostic potentials of CTP, even the latest guidelines do not explicitly recommend this modality, neither for the detection of CAD in general nor for stented patients [2,38]. Until now, there is no consensus of the optimal scanning mode of CTP and the protocols may vary across institutions which hinders the structural implementation of this technique across a broad range of institutions [39]. Additionally, the use of CTP is associated with a higher radiation dose burden and an exact guideline for patient referral to this imaging modality should be drawn up in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that despite the growing evidence supporting the diagnostic potentials of CTP, even the latest guidelines do not explicitly recommend this modality, neither for the detection of CAD in general nor for stented patients [2,38]. Until now, there is no consensus of the optimal scanning mode of CTP and the protocols may vary across institutions which hinders the structural implementation of this technique across a broad range of institutions [39]. Additionally, the use of CTP is associated with a higher radiation dose burden and an exact guideline for patient referral to this imaging modality should be drawn up in the future.…”
Section: Discussionmentioning
confidence: 99%
“…По эффектам и механизмам он подобен аденозину. Дипиридамол также вводят с помощью инфузии, однако за счет более длинного периода полураспада, в отличие от аденозина, для прекращения его действия и купирования симптомов ишемии может потребоваться использование антагониста аденозиновых рецепторов -аминофиллина, поэтому дипиридамол используется реже [10,12].…”
Section: стресс-агентыunclassified
“…Корректировка дозы на массу тела не производится. Благодаря более длительному периоду полувыведения регаденозон можно вводить однократно болюсно, при этом пиковая вазодилатация развивается через 2-4 мин [10,12]. В настоящее время дипиридамол (раствор для инъекций), аденозин и регаденозон не зарегистрированы в Российской Федерации.…”
Section: стресс-агентыunclassified
“…Groothuis et al (42) compared CCTA with MR myocardial perfusion imaging and found that only 42.3% of patients with obstructive coronary arterial disease on CCTA showed myocardial ischemia on MR perfusion. Thus, additional functional assessments, such as fractional flow reserve (FFR) measurements, cardiac single-photon emission computed tomography (SPECT), stress echocardiography, or stress perfusion MR, are needed to determine the indications for revascularization (424344). Recent advances in CT technology have enabled myocardial CT perfusion imaging with high temporal resolution and a reasonable radiation dose.…”
Section: Applications Of Wide-detector Ct In Cardiothoracic Imagingmentioning
confidence: 99%